In Situ Complex with by‐product HCl and Release Chloride Ions to Dissolve Aramid. Issue 19 (2nd July 2018) - Dai, Yu; Cheng, Zheng; Yuan, Yihao; Meng, Chenbo; Qin, Jiaqiang; Liu, Xiangyang
Abstract: Because of the strong hydrogen‐bond interaction among macromolecular chains, the addition of chloride salts is generally needed to offer Cl − ions for the dissolution of aromatic polyamides. In this paper, poly‐(benzimidazole‐terephthalamide) which complexed with by‐product HCl during polymerization (PABI‐HCl) was prepared and imidazole compound as cosolvent was added into dimethylacetamide (DMAc) to dissolve PABI‐HCl. Due to stronger affinity to protons, imidazole compound could in‐situ complex with HCl of PABI‐HCl and form imidazolium hydrochloride. Then imidazolium hydrochloride would ionize and produce much free Cl − ions which acted as stronger hydrogen‐bond acceptor to disrupt interaction among macromolecular chains. As a result, solubility of PABI‐HCl in DMAc was improved significantly in existence of small amount of imidazole compound. Moreover, DMAc‐imidazole mixture was utlized for synthesis of different kinds of aramids and no precipitation was observed with progress of the reaction. So the mixture was suitable to be utlized as solvent for polymerization of aramid. Abstract : Imidazole is selected as co‐solvent for the polymerization of aramid. It can complex with by‐product HCl during polymerization and release Cl − ions as hydrogen‐bond acceptors to disrupt the interaction of aramid.